Physical and Mechanical Properties of Industrial Waste Modified Mortar - Norsuzailina, Mohamed Sutan; Ibrahim, Yakub; Hebron, Jau (Universiti Malaysia Sarawak (UNIMAS), 2013)
This paper presents and discusses the results of the study on physical and mechanical properties of Industrial Waste Modified Mortar (IWMM) in comparison to Unmodified Mortar (UM). Industrial wastes used as ternary cement replacement were Micro Silica (MS) and Finely Ground Waste Vase (FGWV). Porosity and compressive strength of cement based products are the crucial properties that reflect the durability. Results of this study showed incorporation of 15%MS and 20%FGWV as ternary binders reduced 32.8% porosity and increased 4.3% compressive strength of mortar.